Islamic Education and Capitalism: Modern Islamic Education Management in Banten - Ahmad Qurtubi; A. Asari (EduLine: Journal of Education and Learning Innovation, 2022)
Abstract The purpose of the writing is to describe the global capitalism against Islamic education. The findings fall into the discussion of factual and real education environmental research on market demand and industrial management (Islamic education contemporary issues). The techniques used in this research are qualitative research at which the data gained from the deep interview and observation. The techniques of data analyses were applied data reduction (data reduction), data description, discussion and drawing conclusion. The principle of capitalism that only seeks profit personal should not be practiced in the world of education. Rising demand of the education accesses will result in the high cost of education. Islamic education institution should not watch out for the jargon "poor people are forbidden". The findings of the research showed the output of Islamic education, hence the learning outcome of Islamic education (whatever the level), formal, and informal must meet the need to the life-long skill to human values of life. The real connection to the capitalism and Islamic education never be ended to such industrial management and high risk to capital and profit oriented rather than to create high standard religious values.